2000
DOI: 10.1096/fj.00-0359fje
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐inflammatory effects of sodium butyrate on human monocytes: potent inhibition of IL‐12 and up‐regulation of IL‐10 production

Abstract: Cytokines are critical in regulating unresponsiveness versus immunity towards enteric antigens derived from the intestinal flora and ingested food. There is increasing evidence that butyrate, a major metabolite of intestinal bacteria and crucial energy source for gut epithelial cells, also possesses anti-inflammatory properties. Its influence on cytokine production, however, is not established. Here, we report that butyrate strongly inhibits interleukin-12 (IL-12) production by suppression of both IL-12p35 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
267
5
2

Year Published

2002
2002
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 395 publications
(287 citation statements)
references
References 56 publications
(65 reference statements)
13
267
5
2
Order By: Relevance
“…The ileum wall is interstratified with Peyer's patches, parts of the gut-associated lymphoid tissue. Cells from these patches have been shown to release anti-inflammatory cytokines such as IL10 after stimulation with probiotics, prebiotics or fermentation products thereof (Sä emann et al, 2000;Hosono et al, 2003;Roller et al, 2004). Therefore, it seems probable that fermentation products deriving from inulin degradation or secretory molecules from bacteria stimulated by inulin feeding are causative agents in this increase of IL10 expression.…”
Section: Discussionmentioning
confidence: 99%
“…The ileum wall is interstratified with Peyer's patches, parts of the gut-associated lymphoid tissue. Cells from these patches have been shown to release anti-inflammatory cytokines such as IL10 after stimulation with probiotics, prebiotics or fermentation products thereof (Sä emann et al, 2000;Hosono et al, 2003;Roller et al, 2004). Therefore, it seems probable that fermentation products deriving from inulin degradation or secretory molecules from bacteria stimulated by inulin feeding are causative agents in this increase of IL10 expression.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the combination of HDAC inhibitors trichostatin and butyrate have been shown to reduce IFN-␥ production by T cells (24). Leoni et al (10) have demonstrated significant reductions of TNF-␣, IL-1␤, and IFN-␥ in experimental endotoxemia and ConA-induced hepatic injury models with lower doses of SAHA than usually used as an antitumor agent.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, the recently reported ability of n-butyrate to inhibit antigen-specific immune reactivity in vivo indicates a potential clinical relevance (22,23). A central feature of n-butyrate-mediated inhibition of T-cell expansion is the abrogation of IL-2 production (17,24), which appears to be an important determinant of anergy induction. To obtain a better understanding of the mode of bacterial interference, we investigated the molecular mechanisms underlying the inhibition of IL-2 production by n-butyrate.…”
Section: T-cell Receptor (Tcr)mentioning
confidence: 99%